Psychological and CognitivePragmatic Basis of Modus - Yigitaliyeva Zilola Muratovna (Genius Publishing Group, 2022)
In this article we are talking about the modus of formation during communication. In particular, the modus is formed in the content part of the information, further enhancing its coloring property. The article presents a cognitive-pragmatic model of the elements of the linguistic system based on Karl Buhler's semantic model of the function of language units. This model reveals the cognitive and pragmatic aspects of the mode in its place.
Keywords: Modus; language functions; character and subject connection; imagination